2012
DOI: 10.4314/sokjvs.v10i2.8
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the occurrence and spread of Highly Pathogenic Avian Influenza H5N1 in commercial poultry farms in Kano, Nigeria

Abstract: Outbreaks of Highly Pathogenic Avian Influenza (HPAI) subtype H5N1 occurred previously for three consecutive years, 2006, 2007 and 2008 in Kano State, Nigeria, causing heavy economic losses to farmers and the government. It was against this background that risk factors for the occurrence and spread of HPAI H5N1 among commercial poultry farms in the State were evaluated. A total of 64 farms comprising 32 affected (AF) and 32 non-affected (NAF) farms were enrolled for this study. Questionnaires were designed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 31 publications
0
13
1
Order By: Relevance
“…The study revealed that contrary to reports from other states in Nigeria such as Abuja, Plateau and Kano states, poultry farms in Benue state were not concentrated in a particular area but are dispersed which might be due to difference in town planning policy with no designated farm areas in Benue state unlike Kano and Abuja where particular areas are designated for farms (Wakawa, 2012;Balami et al, 2014). Hence the risk of spread of ND and other avian diseases between farms due to close proximity will be reduced and the practice of poor biosecurity by a farm is less likely to endanger the investment of a neighboring farm.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…The study revealed that contrary to reports from other states in Nigeria such as Abuja, Plateau and Kano states, poultry farms in Benue state were not concentrated in a particular area but are dispersed which might be due to difference in town planning policy with no designated farm areas in Benue state unlike Kano and Abuja where particular areas are designated for farms (Wakawa, 2012;Balami et al, 2014). Hence the risk of spread of ND and other avian diseases between farms due to close proximity will be reduced and the practice of poor biosecurity by a farm is less likely to endanger the investment of a neighboring farm.…”
Section: Discussioncontrasting
confidence: 60%
“…The risk of local poultry in introducing NDV to commercial poultry is further supported by previous study indicating that local poultry flocks maintains the NDV in circulation and act as reservoirs and carriers (Assam et al, 2011;Lawal et al, 2016). This study also revealed that some poultry farms have in their vicinity ponds and dams a converging point for wild water fowls, ducks and other migratory birds which have been identified as reservoirs of ND virus which may also increases the risks of NDV introduction and maintenance (Echeonwu et al, 1993;Oladele et al, 2012;Wakawa et al, 2012). Some of the poultry farms have dense vegetation within the farms and also abandoned materials near poultry houses.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…There are published reports on HPAI H5N1 in commercial and village chickens (Thomas et al 2005;Wakawa et al 2012;Musa et al 2013;Alders et al 2014), but there is paucity of such information on avian influenza in pastoral bird flocks, which often scavenge and are potentially exposed to avian influenza virus infections. To the best of our knowledge, this study was the first to investigate knowledge/awareness of and biosecurity measures for HPAI H5N1 in pastoral poultry flocks.…”
Section: Discussionmentioning
confidence: 99%